Rancang Bangun Multimedia Interaktif pada Materi Jenis Usaha dan Kegiatan Ekonomi Kelas V Sekolah Dasar - Zilfa Amalia Tsany; Deti Rostika; Muh. Husen Arifin (Pusat Riset dan Inovasi Nasional, 2023)
This research is about the design and development of interactive multimedia to introduce types of businesses and economic activities. This research is motivated by the problem of learning media which at the moment is still fixated on teachers and books. Another problem is the lack of knowledge and ability of teachers in introducing types of businesses and economic activities and the condition of students who have a great interest in using digital technology-based learning media. Thus, this research aims to create an Interactive Multimedia as a facilitator for students in learning the material of business types and economic activities. This research uses the Design and Development (D&D) research model, with Analyze, Design, Development, Implementation, and Evaluation (ADDIE) research procedures. This research involved experts and users. The results of the assessment from the expert's point of view for the feasibility of interactive multimedia is very feasible to be implemented in learning.